2016
DOI: 10.1017/s0025315416001326
|View full text |Cite
|
Sign up to set email alerts
|

Spatial and temporal trends in order richness of marine phytoplankton as a tracer for the exchange zone between coastal and open waters

Abstract: (2017). Spatial and temporal trends in order richness of marine phytoplankton as a tracer for the exchange zone between coastal and open waters.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 65 publications
1
4
0
Order By: Relevance
“…Average richness per sample was 37 ASVs, comparable to estimates observed in other coastal ecosystems (e.g., Ollison et al 2022). Diatom ASV richness changed with season, in alignment with previous work in coastal systems that showed significant seasonal shifts in richness attributed to local environmental conditions (Jung et al 2017; Gran‐Stadniczeñko et al 2019). Furthermore, ASV richness in NBay was not linearly correlated with changes in Chl a concentration, even during diatom blooms when the water column can be numerically dominated by one or two species (Karentz and Smayda 1984; Canesi and Rynearson 2016).…”
Section: Discussionsupporting
confidence: 87%
“…Average richness per sample was 37 ASVs, comparable to estimates observed in other coastal ecosystems (e.g., Ollison et al 2022). Diatom ASV richness changed with season, in alignment with previous work in coastal systems that showed significant seasonal shifts in richness attributed to local environmental conditions (Jung et al 2017; Gran‐Stadniczeñko et al 2019). Furthermore, ASV richness in NBay was not linearly correlated with changes in Chl a concentration, even during diatom blooms when the water column can be numerically dominated by one or two species (Karentz and Smayda 1984; Canesi and Rynearson 2016).…”
Section: Discussionsupporting
confidence: 87%
“…from Lake IJssel, receiving water from the river Rhine, and from the coastal waters of the North Sea connected to the tidal basins via tidal inlets between the barrier islands (Duran-Matute et al, 2014;Postma, 1950;Ridderinkhof et al, 1990). Field measurements and information from reflectance images retrieved by means of remote sensing suggest the presence of a coastal zone seaward of the barrier islands in which such an exchange of water, nutrients and organic matter between the Wadden Sea and the North Sea takes place (Jung et al, 2016;Postma, 1981;Postma, 1984;van Raaphorst et al, 1998;Visser et al, 1991).…”
Section: Highlightsmentioning
confidence: 99%
“…We conclude that this i-trait could represent adaptation to different water basin conditions (nutrient availability and salinity), which are different for the Wadden Sea and the Southern part of the North Sea (van Beusekom et al, 1999;van Beusekom and de Jonge, 2002). Such interpretation is likely, as it is being considered in the scientific literature (Carstensen et al, 2015;Jung et al, 2017).…”
Section: Successful Aggregation Of Phytoplankton Datasetsmentioning
confidence: 80%
“…Significant declining estimations of functional diversity in the West Wadden Sea are in line with recent reports (Wolff et al, 2010;van Beusekom et al, 2019;Jacobs et al, 2020) and showed the ever prevalence of fastgrowing nutrient opportunist phytoplankton species in this ecosystem. Additionally, the difference in the functional diversity trends of the Southern North Sea stations might be explained by the existence of a 'line-of-no-return' off the sand barrier islands of the Wadden Sea (Postma, 1984;Jung et al, 2017), which might isolate off-shore stations and their phytoplanktonic community.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation